Molybdenum Carbide as a Highly Selective Deoxygenation Catalyst for Converting Furfural to 2‐Methylfuran. Issue 8 (22nd April 2014) - Xiong, Ke; Lee, Wen‐Sheng; Bhan, Aditya; Chen, Jingguang G.
Abstract Selectively cleaving the CO bond outside the furan ring of furfural is crucial for converting this important biomass‐derived molecule to value‐added fuels such as 2‐methylfuran. In this work, a combination of density functional theory (DFT) calculations, surface science studies, and reactor evaluation identified molybdenum carbide (Mo2C) as a highly selective deoxygenation catalyst for converting furfural to 2‐methylfuran. These results indicate the potential application of Mo2C as an efficient catalyst for the selective deoxygenation of biomass‐derived oxygenates including furanics and aromatics.